Safety and feasibility of En‐bloc holmium laser enucleation for very large prostates (> 200 cc) with trainee involvement - Feres C. Maluf; Ansh Bhatia; Archan Khandekar; Diana M. Lopategui; Joao G. Porto; Ryan R. Chen; Jean C. Daher; Mohamadhusni Zarli; Robert Marcovich; Hemendra N. Shah (BJUI Compass)
Abstract Objectives To evaluate the safety and feasibility of “en‐bloc” Holmium Laser Enucleation of the Prostate (HoLEP) with trainee involvement in patients with prostates larger than 200 cc. Patients and Methods A retrospective analysis was conducted on patients undergoing HoLEP using the “en‐bloc” technique for prostate sizes > 200 cc between July‐2017 and December‐2023 at an academic teaching hospital. Perioperative data was collected, including patient demographics, clinical parameters, operative details and functional outcomes. Patients who continued to experience incontinence at 1 year were further followed up at 2 years to update their continence status. Sub‐group analysis was performed to compare outcomes between patients with preoperative prostate size of 200–300 cc and > 300 cc. Results The analysis included 89 patients with a mean age of 73.12 ± 8.10 years. Preoperative prostate weight ranged from 200 to 401 cc with a median of 245 cc, and median PSA was 7.71 ng/ml. Median operative time was 218.5 minutes, and median enucleated prostate volume was 164.2 cc. Median postoperative PSA was 0.4 [0.21–0.78] ng/ml. At 1‐year follow‐up, mean IPSS was 1 ± 2.4, Qmax was 27.03 ± 11.57 ml/s and PVR was 21.6 ± 28.6 ml. Postoperative complications included blood transfusion (5.6%), acute renal injury (4.5%), urinary tract infection (2.2%), postoperative urinary retention (2.2%) and urethral stricture (5%). Although transient urinary incontinence was noted in 41.6% at 1–3‐months, complete continence was achieved in 83.3% and 96.3% at 1 and 2 years postoperatively, respectively. Subgroup analysis showed significant differences in operative time and enucleated weight between prostates 200–300 cc and > 300 cc, but no significant differences in postoperative IPSS, PVR or Qmax at 3‐months. Conclusion “En‐bloc” HoLEP is a feasible and safe procedure for prostates larger than 200 cc, demonstrating favourable perioperative and functional outcomes despite the extended operative times and involvement of trainees.